Médiation et mise en scène de Vinformation dans le discours de vulgarization scientifique - Sabban, Annette (Studia Romanica Posnaniensia, 2007)
The present study examines texts about computer viruses from French, Spanish and German popular scientific journals. The first part of the paper shows how these texts make systematic use of concepts and expressions drawn from other domains of discourse. The second part of the paper focusses on a subgroup of the linguistic means employed, i.e. metaphorical expressions, and discusses their functions in the texts under discussion. These functions can be assigned to two groups, in that they either mediate new information or make the message more effective on the rhetorical level. The paper concludes with a discussion of some writer strategies used for activating other semantic domains as a prerequisite for achieving a particular rhetorical effect.